The Effect of Strength Training on Undetected Shoulder Pathology in Asymptomatic Athletes: An MRI Observational Study - Emil Noschajew; Alexander Azesberger; Felix Rittenschober; Amadeus Windischbauer; Michael Stephan Gruber; Reinhold Ortmaier (MDPI AG, 2022)
Background: Data on the effects of weight training on joint morphology are mostly restricted to muscle gain. However, in many circumstances, it is not stated if there are negative consequences for the joints and their surrounding components. This study was conducted to explore whether long-term excessive resistance training (RT) causes hidden pathological alterations in the shoulder. Methods: A total of eleven asymptomatic sportsmen (22 shoulders) underwent clinical and radiological examination of both shoulder joints. All participants had engaged in bodybuilding for at least four years, at least three times per week, and for at least four hours per week. All participants were examined clinically using the Constant Murley Score (CMS), Simple Shoulder Test (SST), UCLA Activity Test, and a specially designed questionnaire. All participants received a bilateral shoulder MRI. The MRI scans were checked for pathology using a checklist. Results: Maximum scores were observed for the SST and UCLA Activity Test. The CMS was 97.7 points on average (range, 87-100). RT had been conducted for a mean of 10.7 years (range, 4-20), for an average of 8.8 h a week (range, 4-12). MRI examinations revealed two supraspinatus tendinopathies (9.1%), one labral change (4.5%), three humeral tuberosity cysts (13.6%), fourteen acromioclavicular (AC) joint hypertrophies (63.6%), five AC joint osteophytes (22.7%), and ten signs of AC joint inflammation (45.5%). Conclusions: The research results show that strength is associated with MRI-documented AC joint pathology. However, it appears that RT may not negatively affect other anatomical structures of the shoulder.